Three Essays in Empirical Asset Pricing - QU, Shanshan (2021)
Inventory investment is volatile and procyclical, the inventory-sales ratio is persistent and countercyclical (Bils & Kahn, 2000; Blinder, 1986; Christiano, 1988), this is one of the stylized facts documented in the macroeconomic inventory behavior studies. Blinder (1986) states: “business cycles, are, to a surprisingly large degree, inventory cycles”. This thesis comprises three independent essays analyzing the inventory-based return predictors, inventory investment and the inventory-sales ratio, and the robustness of twelve fundamental-based anomalies.